2021
DOI: 10.3390/pharmaceutics13070938
|View full text |Cite
|
Sign up to set email alerts
|

The Stimulating Effect of Rosmarinic Acid and Extracts from Rosemary and Lemon Balm on Collagen Type I Biosynthesis in Osteogenesis Imperfecta Type I Skin Fibroblasts

Abstract: Rosemary extract (RE) and lemon balm extract (LBE) attract particular attention of pharmacists due to their high therapeutic potential. Osteogenesis imperfecta (OI) type I is a heritable disease caused by mutations in type I collagen and characterized by its reduced amount. The aim of the study was to evaluate the effect of the extracts and rosmarinic acid (RA) on collagen type I level in OI skin fibroblasts. Phytochemical analysis of RE and LBE was carried out by liquid chromatography–photodiode array detecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 61 publications
0
9
0
Order By: Relevance
“…Rosmarinic acid, according to its properties, can be considered a promising candidate for use in multifunctional sunscreens, acting against free radicals and as an effective antagonist in lipid peroxidation [21][22][23][24][25]. The DoE 2 3 was used to develop the O/W emulsions (F1 to F8).…”
Section: Discussionmentioning
confidence: 99%
“…Rosmarinic acid, according to its properties, can be considered a promising candidate for use in multifunctional sunscreens, acting against free radicals and as an effective antagonist in lipid peroxidation [21][22][23][24][25]. The DoE 2 3 was used to develop the O/W emulsions (F1 to F8).…”
Section: Discussionmentioning
confidence: 99%
“…Phytochemicals, due to their natural origin, low toxicity, as well as many valuable biological and pharmacological properties, are of wide interest among researchers as potential drugs with a high therapeutic and preventive potential for many diseases. R. officinalis is a polyphenol-rich source constituents such as luteolin and apigenin derivatives, caffeic acid derivative (rosmarinic acid) and other such as diterpenes (rosmanol isomers), detailed qualitative analysis of which was presented earlier [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Rosemary ( Rosmarinus officinalis L., Lamiaceae) is a rich source of many bioactive polyphenol compounds with a wide range of biological activities, such as antioxidant, antimicrobial, anti-inflammatory, antidiabetic and anticancer [ 33 , 34 ]. In our previous study, we showed a beneficial effect of rosemary extract (RE) on the biosynthesis of type I collagen in OI type I fibroblasts with quantitative type I collagen defect [ 35 ]. This time we examined whether RE could reduce the accumulation of mutant collagen in the fibroblasts of two patients with severe type III and two patients with lethal type II OI carrying mutations in α(I) chain.…”
Section: Introductionmentioning
confidence: 99%
“…An important achievement of our research was the disclosure that RA at the concentration of 100 µM can provide complete or partial protection against these BP-3 induced adverse effects on the skin cells and the macromolecules building the skin ECM. In the previous study we proved that this polyphenolic compound itself can directly affect the transcription, increasing type I collagen or reducing collagen-degrading enzymes in both normal and OI human skin fibroblasts [ 36 , 66 ]. We have also given some examples of indirect protective effect of RA on collagen by influencing the factors regulating its biosynthesis, e.g., extracellular signal-regulated protein kinases 1 and 2 [ 36 ].…”
Section: Discussionmentioning
confidence: 99%